Cross-Cultural Adaptation of Indonesian Pre-Service EFL Teachers in Early Childhood Education Institutions in Thailand: A Qualitative Study - Dinda Sakila; Erizar Erizar; Rena Juliana (Jurnal Ragam Pengabdian, 2026)
This study aims to explore the cross-cultural adaptation process experienced by Indonesian pre-service EFL teachers when teaching English at early childhood education institutions in Thailand and its impact on teaching effectiveness. This study uses a qualitative descriptive approach based on Kim’s stress–adaptation–development theory (2017). Purposive sampling technique was used to select eight Indonesian female pre-service EFL teachers based on their experience in international teaching practice. Data were collected through semi-structured interviews and analysed using thematic analysis through coding, categorization, and theme interpretation. The results showed that differences in language and student learning styles were the main obstacles in the early stages of adjustment. However, the participants gradually adjusted their teaching methods by using nonverbal communication, songs, games, movements, and experience-based approaches. This adjustment increased student engagement, improved classroom interaction, and strengthened the relationship between teachers and students. Support from mentors and the school environment also played a role in facilitating the adjustment process. Overall, cross-cultural adaptation contributed positively to the quality of English language teaching in early childhood education. This study shows that pedagogical adaptability and intercultural competence are essential for pre-service EFL teachers when facing multilingual classroom environments in early childhood education.